2022
DOI: 10.1097/md.0000000000030599
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of maternal sepsis: A retrospective study of whole pregnancy period

Abstract: Maternal sepsis results in poor outcomes such as fetal or maternal death. The incidence and mortality rates of maternal sepsis vary in different places because of differences in economic development, race and medical conditions. Identifying the clinical features and determining possible mechanisms for avoiding morbidity and preventing poor outcomes would benefit committed patients. Therefore, this was an epidemiological study at a maternity transfer center in Southeast China that aimed to identify local diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Pregnant women are at high risk of contracting influenza or bacterial infection during the flu season. Once infection occurs, it is easy for pregnant women to trigger a systemic inflammatory response 1,3,19,20 . The use of peripheral blood biomarkers for early diagnosis of infection in pregnant women is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women are at high risk of contracting influenza or bacterial infection during the flu season. Once infection occurs, it is easy for pregnant women to trigger a systemic inflammatory response 1,3,19,20 . The use of peripheral blood biomarkers for early diagnosis of infection in pregnant women is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Once infection occurs, it is easy for pregnant women to trigger a systemic inflammatory response. 1 , 3 , 19 , 20 The use of peripheral blood biomarkers for early diagnosis of infection in pregnant women is essential. Pregnant women are a unique population and are less studied in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream infection in pregnancy or during the perinatal period is still a significant clinical problem with high morbidity and mortality, even in developed countries ( Waterstone et al, 2001 ; Surgers et al, 2013 ; Zou et al, 2021 ). There are some studies focusing on maternal infectious diseases in mainland China ( Lin et al, 2021 ; Zou et al, 2021 ; Zhong et al, 2022 ) but only one published study focused on perinatal BSI could be found ( Zou et al, 2021 ). Very little is known about various aspects of maternal bacteremia in relation to changes of microbiological epidemiology and obstetric outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is a major cause of morbidity and mortality during pregnancy, both for the pregnant woman and the fetus [1]. Within the existing literature, the majority of studies have taken a broad approach, encompassing all causes of sepsis in pregnant women [2][3][4][5], and very few have specifically examined the impact of urinary tract infections (UTIs), particularly febrile infections, on the development of sepsis and its consequences for both mother and child. Similarly, factors associated with the occurrence of sepsis have been studied regardless of the site of primary infection [2,6,7].…”
Section: Introductionmentioning
confidence: 99%